2020
DOI: 10.1021/acs.jpcc.0c03489
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Role of Shape and Size in Second-Harmonic Scattering from Gold Nanoprisms

Abstract: Gold nanoparticles are widely used in different fields. They are currently under extensive investigation with regard to their linear and nonlinear optical properties. So far, nanoparticles with centrosymmetrical shapes, such as nanospheres or nanorods, have received the main attention. In this work, the properties of gold nanoprisms exhibiting a highly noncentrosymmetrical threefold symmetry are investigated with hyper-Rayleigh scattering (HRS). Aqueous solutions of gold nanospheres and nanoprisms with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…In this report, Hyper Rayleigh Scattering (HRS), the incoherent scattering of SHG light, is investigated for an aqueous suspension of 50 nm diameter AuNPs to assess the sensing potential toward copper­(II) ions. The study entails the use of intensity and light polarization analysis of the scattered SHG intensity. Although the method in its details requires a close scrutiny of the nonlinear optical phenomenon, it appears that its setup into a sensing method remains accessible for a simple operation.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, Hyper Rayleigh Scattering (HRS), the incoherent scattering of SHG light, is investigated for an aqueous suspension of 50 nm diameter AuNPs to assess the sensing potential toward copper­(II) ions. The study entails the use of intensity and light polarization analysis of the scattered SHG intensity. Although the method in its details requires a close scrutiny of the nonlinear optical phenomenon, it appears that its setup into a sensing method remains accessible for a simple operation.…”
Section: Introductionmentioning
confidence: 99%
“…12 This has been done for lithographed nanoprism arrangements with D3h symmetry 13,14 and for colloidal nanoprisms in solution. 15 Obtaining materials with an octupolar response is interesting, 16,17 both from a fundamental point of view and for applications, since the SHG intensity has a very characteristic polarization pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been attempted, for instance, with heterogeneous NP dimers. Another possibility is to develop the octupolar β (3) component with a 3-fold symmetry while maintaining a low dipole . This has been done for lithographed nanoprism arrangements with D 3 h symmetry , and for colloidal nanoprisms in solution . Obtaining materials with an octupolar response is interesting , both from a fundamental point of view and for applications, since the SHG intensity has a very characteristic polarization pattern.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used method to enhance the emission from fluorophores is a technique known as surface-enhanced fluorescence (SEF). It has been shown that plasmon supporting materials such as gold and silver can be used to boost the Raman and fluorescence signal by typically several orders of magnitude when the analyte molecule is positioned in close proximity to the metal (typically 10–90 nm from the surface). The use of metal-based templates for the improved detection of biomolecules has several disadvantages; noble metals can be expensive, difficult to manufacture (lithography methods must be used to ensure reproducibility), lack biocompatibility (particularly in the case of silver), and may induce photocatalytic side reactions in analytes . For that reason, fabricating sensing platforms based on dielectric materials that can enhance the fluorescence signal strength from a fluorophore is of enormous interest.…”
Section: Introductionmentioning
confidence: 99%